Measuring User Satisfaction Online-KRS Using End User Computing Satisfaction Method - Wika Aditya Ramadhan; Setiyowati Setiyowati; Bebas Widada (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2021)
Evaluation of User Satisfaction with the Online KRS System at XYZ Health College using the End User Computing Satisfaction method. XYZ Health College in the KRS process has been supported by the KRS Online information system, but the KRS Online user satisfaction level has never been measured. The purpose of this study was to determine the level of user satisfaction of KRS Online College of Health XYZ in terms of several factors, namely content, accuracy, form, ease of use, and timeliness in assessing user satisfaction of KRS Online. The results of the research using instrument tests, data quality tests, multiple linear regression analysis, coefficient of determination, t test and f test are known based on the results of the analysis that the effect of the independent variable on the dependent variable is expressed by the coefficient of determination (R2) which is 0.471 or 47.1% . And the value > Fcount (13.904) > Ftable (2.76) so that the content, accuracy, form, ease of use and timeliness together have an effect on satisfaction.